Preliminary investigation of primary sludge hydrolysis - Dauknys, Regimantas; Mažeikienė, Aušra; Haluza, Anna; Halauniou, Illia; Yushchenko, Victor (International Conference “Environmental Engineering”, 2017)
One of reasons of noneffective biological nutrient removal from wastewater is lack of readily biodegradable organic matter. This problem could be solved by application of sludge hydrolysis process. The conditions for hydrolysis of primary sludge could be created performing the recirculation of the primary sludge and ensuring the required sludge retention time. In the period of preliminary investigation, the following conditions were created in the primary sedimentation tank of Vitebsk WWTP: average sludge recirculation was 4.8 % of the inlet flowrate to the sedimentation tank and average SRT was 5 days. Obtained results showed that hydrolysis process allowed improving the ratio between organic matter and nutrients in wastewater.